The effect of work environment, job satisfaction and organisational commitment on organizational citizenship behavior - Askar Jaya; Yenni Marliza; Ampia Wartati (Jurnal Mantik, 2023)
The organizational citizenship behavior (OCB) implemented at the Sungai Penuh City Culture and Tourism Office has not been implemented optimally. This results in bad relations between employees. This research aims to determine the influence of job satisfaction, work environment and quality of work life on Organizational Citizenship Behavior (OCB) of employees at the Sungai Penuh City Culture and Tourism Office. This research uses qualitative and quantitative research methods, where the sampling technique uses a total sampling technique, with a total sample of 37 employees of the Sungai Penuh City Culture and Tourism Office. The analysis technique is multiple regression analysis. The results of this research are that, both partially and simultaneously, the work environment, job satisfaction and Organizational Commitment have a positive and significant effect on the Organizational Citizenship Behavior (OCB) of employees at the Sungai Penuh City Culture and Tourism Service.